SEM/EDX characterization and profiling of particulate matter of cefuroxime powder for injection - Bulatao, Bryan Paul I. 1986-
Current pharmaceutical standards enforce limits to the quantity of subvisible particulate matter present in injections. However, this pharmaceutical requirement is insufficient, as it does not take into account the nature and source of particulate matter. This study aimed to characterize and profile the particulate matter present in four brands of Cefuroxime powder for injection. The constituted solutions were filtered using a 0.45 µm poletherulfone membrane filter to isolate matter. SEM/EDX was used to identify the particulate matter. The identification of the particulate matter was a result of integrating its size, morphology, chemical composition, and a comparison of the SEM/EDX outputs of the particulate matter with that of the known materials. This study identified glass chips, glass lamellae, rubber fragments, polytetrafluoroehtylene, fluorinated film coating, dolomite, paint clay, undissolved Cefuroxime, silica powder, talc, calcium silicate, SS 316L, a magnesium-rich particulate and an unclassified fiber. Brand D contained the most number of particulate matter types. It was evident that glass from the vials was the most common particulate matter followed by rubber, and then calcium silicate. The possible sources of particulate matter were identified through literature review and experimentation. However, there was no discernible trend in the type of particulate matter identified in the three different experimental conditions. Hence, the sources of the particulate matter could net be precisely identified. The profile of the particulate matter may serve as a reference tool for particulate matter testing and research. Further studies must also be made to assess and verify the precise mechanism of formation of the particulate matter found in the various brands of Cefuroxime powder for injection.
Thesis (Master of Science in Industrial Pharmacy)--University of the Philippines Manila, December 2014.
Available to the general public.
Keywords: Cefuroxime; Particulate Matter